A Practical Application of FMEA for IT Project Prioritization : a Case Study at Manufacturing Company - Diena Novitasari; Komarudin Komarudin; Akhmad Hidayatno (Proceeding International Conference on Information Technology and Business, 2019)
This research aims to develop a method for information technology (IT) project prioritization that is very easy for a user through a case study in a manufacturing company. This researchused descriptive qualitative research based on survey data from unstructured and semistructured interviews with system development managers. Furthermore, the applicability of the developed method is assessed. A combination of importance analysis and risk analysis using failure mode and effect analysis (FMEA) is useful and applicable to this company. The risk that is considered in this study is the risk of a delayed project for the company. This study contributes to the relevant literature by proposing a very applicable IT project prioritization method.Keywords: IT Project Prioritization, Risk Analysis, FMEA, Importance Analysis